Contribution of cerebrospinal fluid antibody titers and sex to acute cerebral blood flow in patients with anti-NMDAR autoimmune encephalitis - Miao, Ailiang; Wang, Kai (Frontiers in Immunology, 2024)
The objective of this study was to elucidate the contribution of cerebrospinal fluid (CSF) antibody titers (AT) in and sex to acute cerebral blood flow (CBF) in patients diagnosed with anti-N-methyl-d-aspartate receptor autoimmune encephalitis (NMDAR AE).Forty-five patients diagnosed with NMDAR AE were recruited from Dec 2016 to Jan 2023. The acute CBF in patients with NMDAR AE at the early stage of the disease was analyzed using arterial spin labeling. The groups were compared based on CSF AT and sex. The connectivity of the CBF in region of interest was also compared between groups.The patients with different CSF AT exhibited varied brain regions with CBF abnormalities compared to the healthy subjects (P=0.001, cluster-level FWE corrected). High antibody titers (HAT) in CSF contributed to more brain regions with CBF alterations in female patients than in female patients with low antibody titers (LAT) in CSF (P=0.001, cluster-level FWE corrected). Female patients with HAT in CSF displayed more decreased CBF in the left post cingulum gyrus, left precuneus, left calcarine, and left middle cingulum gyrus than the male patients with same AT in CSF (P=0.001, cluster-level FWE corrected).All patients with NMDAR AE showed increased CBF in the Putamen_L and Amygdala_L and decreased CBF in the Precuneus_R, which suggests these are diagnostic CBF markers for NMDAR AE.CSF AT and sex contributed to CBF abnormalities in the patients diagnosed with NMDAR AE. Altered CBF might potentially serve as the diagnostic marker for NMDAR AE.